2002
DOI: 10.1046/j.1440-1681.2002.03744.x
|View full text |Cite
|
Sign up to set email alerts
|

Choleresis and inhibition of biliary lipid secretion induced by piperacillin in the rat

Abstract: 1. The effects of the administration piperacillin on bile flow and biliary lipid secretion were studied in male Wistar rats. 2. Intravenous injection of piperacillin at doses ranging from 0.3 to 3.0 mmol/kg bodyweight led to an increase in its biliary concentration and excretion rate. Maximal biliary excretion was reached at a dose of 2.0 mmol/kg piperacillin. 3. Excretion of the antibiotic into bile was associated with a marked choleresis. A linear relationship was observed between bile flow and piperacillin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Such a steep gradient likely causes the osmotic traction of water from the blood to the bile via the tight junctions of hepatocytes and cholangiocytes. If PCG excretion is directly related to choleresis, the choleretic index can be calculated as 21.8 l/mol PCG excreted into bile, and this is comparable with the other choleretics reported previously (13,14,36). However, the biliary excretion of PCG itself was not exactly correlated with the bile flow rate (r 2 ϭ 0.768), suggesting that other transported ion(s) may be the additional driving force of the choleretic phenomenon.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such a steep gradient likely causes the osmotic traction of water from the blood to the bile via the tight junctions of hepatocytes and cholangiocytes. If PCG excretion is directly related to choleresis, the choleretic index can be calculated as 21.8 l/mol PCG excreted into bile, and this is comparable with the other choleretics reported previously (13,14,36). However, the biliary excretion of PCG itself was not exactly correlated with the bile flow rate (r 2 ϭ 0.768), suggesting that other transported ion(s) may be the additional driving force of the choleretic phenomenon.…”
Section: Discussionsupporting
confidence: 87%
“…Verkade et al (35) reported that intravenous administration of ampicillin (180 mol/kg) to rats induced choleresis, but this was not observed in Mrp2-deficient TR Ϫ rats. Gonzalez et al (14) reported that 0.3-3 mmol/kg piperacillin also induced choleresis in rats, and this was mainly explained by the stimulation of BSIDF. Biliary excretion of ␤-lactam antibiotics also appears to be mediated by Mrp2, because excretion in bile was dramatically reduced in Mrp2-deficient rats (29,35).…”
mentioning
confidence: 99%
“…Experimental studies in rats showed that piperacillin decreased biliary phospholipid secretion, pointing toward an inhibitory effect of the drug preferably on a canalicular transporter. 15 MRP2 emerged as the best guess as the putative target for the interaction, as both piperacillin and phospholipids are substrates for human MRP2. If hepatic MRP2 seems to be the most probable target, one cannot rule out an inhibitory effect on renal MRP2, leading to a shift in the fraction of vincristine normally eliminated renally (10% to 20%) from the kidney to the liver, thus causing or amplifying overexposure.…”
Section: Discussionmentioning
confidence: 99%